Malaysia’s first record of the elusive scaleless spiny waspfish Ablabys gymnothorax Chungthanawong & Motomura 2018 (Perciformes, Synanceiidae, Tetraroginae) - Danial Hariz Zainal Abidin; Siti Azizah Mohd. Nor; Ying, Giat Seah; Mohd Sharol Ali; Nur Athirah Abdul Latiff; Cabebe-Barnuevo, Roxanne A.; Motomura, Hiroyuki; Tun Nurul Aimi Mat Jaafar (Penerbit Universiti Kebangsaan Malaysia, 2024)
We document the first record of the Scaleless Spiny Waspfish, Ablabys gymnothorax Chungthanawong & Motomura 2018 (Perciformes, Synanceiidae, Tetraroginae), from the east coast of Peninsular Malaysia. This species was previously documented in Japan, Taiwan, and Vietnam. Two specimens were collected with one was trawled from the South China Sea Exclusive Economic Zone (EEZ) during a bottom trawl survey and the other was collected at Kuantan fish landing port, Pahang. These findings not only document the first country record but also suggest A. gymnothorax manifests a broader geographic distribution across the Indo-Pacific than previously recognized. Diagnostic characters are provided for both documented individuals, alongside detailed morphometric and meristic data.